PENGARUH CAPITAL ADEQUACY RATIO (CAR), FINANCING TO DEPOSIT RATIO (FDR) DAN NON PERFORMING FINANCING (NPF) TERHADAP PROFITABILITAS: (STUDI KASUS PADA BANK UMUM SYARI’AH DI INDONESIA 2015-2019) - Yulian, Tri Nurindahyanti; Ciptaningsih, Rokhmah Agus; Andriyani , Siti (JURNAL EKONOMI, 2022)
This study aims to analyze the Capital Adequacy Ratio (CAR) Financing To Deposit Ratio (FDR) and Non Performing Financing (NPF) Against Profitability at Islamic Commercial Banks in Indonesia. The research period is 5 years, starting from 2015 to 2019. The sample selection technique uses the purposive sampling method, the type of data used is secondary data and the total sample used in this study is 7 Islamic commercial banks, the analysis method is to test the dependent variable and the independent variable used is multiple linear regression. The results of this study indicate that the Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR) has no effect on Return On Assets (ROA) and Non-Performing Financing (NPF) has no effect on Return On Assets (ROA) in Islamic Commercial Banks in Indonesia. 2015-2019.